Evaluation of serum and gingival crevicular fluid microRNA-223, microRNA-203 and microRNA-200b expression in chronic periodontitis patients with and without diabetes type 2 - Elazazy, Ola; Amr, Khalda; Abd El Fattah, Abeer; Abouzaid, Maha (Archives of oral biology, 2021)
[Display omitted] •miRNAs levels were compared in serum and GCF of individuals with periodontitis with and without diabetes.•miRNA-223 and miRNA-200b were up-regulated in serum and GCF of periodontitis and periodontitis + type 2 diabetes groups.•miRNA-203 was down-regulated in serum and GCF of periodontitis and periodontitis + type 2 diabetes groups.•Serum miRNAs may be considered promising biomarkers of periodontitis associated to type 2 diabetes. microRNA dysregulation is a reported feature of multiple pathologies, including periodontal disease, as demonstrated on cell lines, in animal models, and tissues biopsies, but serum and gingival crevicular fluid microRNA expression data in humans is scarce, especially with the diabetes (type 2) systemic complication. To assess serum and gingival crevicular fluid relative quantification levels of miR-223, miR-203, and miR-200b in chronic periodontitis and type 2 diabetic chronic periodontitis patients to address their possible implication in chronic periodontitis pathogenesis and its systemic complications and also to correlate their differential expression with some inflammatory (serum tumor necrosis factor-α and interleukin-10) parameters. Sixty subjects were recruited and divided into three groups; chronic periodontitis (n = 20), type 2 diabetic chronic periodontitis (n = 20), and healthy control (n = 20). Both serum and gingival crevicular fluid were collected from each participant for miRNA expression analysis and serum inflammatory parameters assessment. A significant increase in the relative quantification levels of miR-223 and miR-200b were detected in patient groups along with a positive correlation with tumor necrosis factor-α. However, miR-203 was significantly decreased in patient groups associated with a negative correlation with tumor necrosis factor-α. miR-223 and miR-200b have a potential role in chronic periodontitis pathogenesis associated with type 2 diabetes, with the ability to induce tumor necrosis factor-α secretion, while miR-203 might have a protective and healing role due to the negative correlation with the serum tumor necrosis factor-α levels found. Therefore, they may be considered as a promising therapeutic target and effective serum disease biomarkers.